Respuesta :
Answer:
yes, it does
Step-by-step explanation:
point (-1, -1)
- y=4x+3
if (-1, -1) lies on this line, it will make below equation correct:
- -1=4*(-1)+3
- -1=-4+3
- -1=-1
Answer is yes
Answer:
Yes it does.
Step-by-step explanation:
For (-1, -1) to lie on the line y= 4x + 3 ; that would mean substituting x=-1 into the expression we should be able to get y=-1 so let's test that.
Substituting x=-1 in y= 4x + 3;
we have : y= 4(-1)+ 3 = -4 +3 = -1;
Since y=-1 tallies with the point (-1, -1)